Florestan Fernandes National School and the political education of rural landless workers - Aline de Jesus Peixinho; Beatriz Vieira Barone; Mario Borges Netto (Universidade Federal do Norte do Tocantins, 2020)
The research objective is to pose theoretical analysis about the educational basis of the Landless Workers' Movement (Movimento dos Trabalhadores Rurais Sem Terra - MST), expressed by educational actions and the organization of Florestan Fernandes National School (Escola Nacional Florestan Fernandes - ENFF). Therefore, we sought to relate the educational principles of the movement to the marxist and marxian theoretical contributions. The chosen methodological framework was bibliographic research, whose main references were Karl Marx, Friedrich Engels, and Vladimir I. Lenin's works, as well as the texts produced by the Movement on education and formation. The research shows that political education has become the center of the educational proposals of the movement, since it enables the constitution of class awareness, capable of contributing to the development of strategies and ways of defending land reform and society transformation. Finally, based on studies about the National School (ENFF), we detected a clarifying theoretical relation between the conception of political party by Lenin and the MST, in which both take the commitment of managing, organizing and educating workers for class struggle, on a perspective of reaching human emancipation and the revolution of an oppressive society.